Effects of test format, self-concept and test anxiety on response changing behaviour among senior secondary school students in Ibadan land (2015)
The study examined the effects of test format (multiple-choice, true or false and matching), self-concept and anxiety on response changing behaviour of senior secondary school students in Ibadan, Oyo State. Two hundred and eighty students in SSS1 and 2 were tested on a 50-item Economics Achievement Test in three formats. Their answers were analyzed for response changes. Results indicated that while multiple-choice, matching and anxiety had significant influence on. response changing, self-concept and true or false items did not.